2014
DOI: 10.7860/jcdr/2014/8248.4508
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology Specific Quality of Life in Vitiligo Patients and Its Relation with Various Variables: A Hospital Based Cross-sectional Study

Abstract: Vitiligo although a cosmetic disease without any symptoms, it carry a significant social stigma especially in Indian society. Data interpretation in this study indicates that vitiligo affects QOL in majority of vitiligo patients and such patients require more aggressive and empathic attitude from a dermatologist to cure/improve this so called chronic cosmetic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 18 publications
8
44
4
2
Order By: Relevance
“…This confirms that vitiligo causes little or no direct physical impairment, it is often considered just as a cosmetic problem. However, the change in appearance caused by this skin disorder can affect a person's emotional and psychological well-being and have In our vitiligo cases, females showed more affection of QoL than males, this is in agreement with many other studies which had reported lower QoL in women with vitiligo (11,19,21,22) and this disagrees with results reported by Zandi et al (1) and Mishra et al (23) who stated that there was no statistically significant difference seen in DLQI between women and men. The larger impact on quality of life in female patients may be due to that they are more emotional and sensitive about their appearance and the potential impact on their marital status.…”
Section: Discussionsupporting
confidence: 78%
“…This confirms that vitiligo causes little or no direct physical impairment, it is often considered just as a cosmetic problem. However, the change in appearance caused by this skin disorder can affect a person's emotional and psychological well-being and have In our vitiligo cases, females showed more affection of QoL than males, this is in agreement with many other studies which had reported lower QoL in women with vitiligo (11,19,21,22) and this disagrees with results reported by Zandi et al (1) and Mishra et al (23) who stated that there was no statistically significant difference seen in DLQI between women and men. The larger impact on quality of life in female patients may be due to that they are more emotional and sensitive about their appearance and the potential impact on their marital status.…”
Section: Discussionsupporting
confidence: 78%
“…Ghajarzadeh et al ., using a linear regression model study, found no predicting roles of age on QoL. Dolatshahi et al ., Ongenae et al ., and others did not find any significant correlation between the DLQI score and age …”
Section: Dermatology Life Quality Index Scores According To the Demogmentioning
confidence: 86%
“…While the impact of dermatological disease on a patient's life has been well recognized, it is only recently that PRO measures have been used as assessment tools in both the management of chronic skin disease and in the evaluation of new treatments . Disease‐specific measures have been developed to assess the impact of atopic eczema, urticaria, contact dermatitis, scleroderma, acne, vitiligo and hidradenitis suppurativa . While all of the PRO measures used in patients with CLE are applicable, they were not included in the concept elicitation phase via use of qualitative interviews to elicit patient burden or concepts relevant to patients with CLE.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatological diseases have long been recognized for their detrimental effect on the quality of life and health status of patients, 17,41,53,[70][71][72][73][74][75][76] thus providing an important opportunity to assess measures needed for the optimal management of patients. While the impact of dermatological disease on a patient's life has been well recognized, it is only recently that PRO measures have been used as assessment tools in both the management of chronic skin disease and in the evaluation of new treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation